Kajian Modalitas dalam MoU Helsinki Nota Kesepahaman Damai antara NKRI dan GAM - Medri Osno (Madah: Jurnal Bahasa dan Sastra, 2019)
The purpose of this study is to find the modalities contained in the Helsinki MoU and the reasons for modalities with the most dominant percentage of emergence. The type of this research is qualitative with descriptive statistics. Data collection uses the method of listening with the note techniques. The data analysis method uses a combination of the method of aggregation and the equivalent method which refers to the Halliday LFS analysis model. The technique used is a technique of sorting direct elements or BUL techniques. The basic technique of the matching method used is the sorting determining element or PUP technique. The modalities that appear in the data are modalization and modulation. The coverage of modalities includes causality, appearance and range. Furthermore, the orientation of modalities is explicit and implicit. Modality is dominated by medium-level probability of 77.3%, high-level proposition of 11.8%, high-level trend of 4.5%, medium-level tendency of 2.7%, and necessity of high and middle level 1.8%. These percentages indicate that most of the action have not been carried out by the Indonesian government and GAM in resolving problems in Aceh.